Alloy selection for service in sulphuric acid : a guide to the use of nickel-containing alloys - Davies, Michael, Dr (Nickel Institute, 2019)
This publication describes the behaviour of nickel-containing alloys and the specific nature of their reactivity with both high and low concentrations, considered separately. The behaviour of other metals commonly used in the manufacture or handling of this acid are also discussed. Table 1 lists the main nickel-containing alloys and their UNS number considered in this introductory publication.